PERSPECTIVE ON INVESTING IN JAKARTA ISLAMIC INDEX WITH FINTECH AS AN INTERVENING VARIABLE (Case Study on Generation Z) - Mukti Prasaja; Gemelthree Ardiatus Subekti; Permatasari Cahyaningdyah; Sifa Rani (Pusat P2M Politeknik Negeri Batam, 2025)
ABSTRACT This study aims to analyze what factors are influential in investing in the Sharia Capital Market focusing on the Jakarta Islamic Index from the perspective of generation Z. The research variables used in this study are the independent variables are financial inclusion, environment, and risk. Furthermore, for the dependent variable, investment interest is used and moderation uses fintech as an intervening variable. The research methodology used is quantitative with causality studies, this is to determine the cause and effect of the hypothesis proposed. The respondents used in the study were generation Z in East Java Province with a research sample using purposive sampling techniques. Data analysis techniques with validity tests and reliability tests and path analysis is used to test the influence between variables directly and indirectly between the variables used. The result of the research is that the influence of risk and fintech on investment interest has a significant positive influence. For the environment of awaraness and financial inclusion on investment interest, it does not have a significant positive influence. In Islamic Financial Inclusion, risk and environmental awareness of investment interest when mediated by fintech produce a higher value than the direct influence of each variable on investment interest. Keywords: